Objectives and tasks of occupational therapy in systemic rehabilitation departments among patients from the RPSO1 group - chronic rehabilitation - Węglarz, Barbara; Ruszkiewicz-Cichosz, Magdalena; Wilk, Tomasz; Czerwiński, Paweł; Kałużna, Anna; Kałużny, Krystian; Hagner, Wojciech; Zukow, Walery (Journal of Education, Health and Sport, 2018)
The main objective of this study is to present the goals and role of occupational therapy in hospital branches of systemic rehabilitation, from the RPS01 group - chronic rehabilitation, which supplements the rehabilitation treatment during hospitalization.